The importance of reminders and patient preferences to improve inhaler technique in older adults with COPD - Barnestein-Fonseca, P.; Cotta-Luque, VM.; Aguiar-Leiva, VP.; Leiva-Fernández, J.; Martos-Crespo, Francisco; Leiva-Fernández, F. (Frontiers in Pharmacology, 2023)
Objectives: Medication non-adherence in patients with chronic obstructive pulmonary disease is common. The aim is to evaluate the efficacy of two interventions to improve the inhalation technique (IT) in patients with pulmonary disease is common. Also determine optimal IT reminder time and to test the role of preferences in the intervention selection. Method: 726 pulmonary disease in common patients (consecutive sampling) from two trials: 1) TECEPOC-study (patients’ preference trial/comprehensive cohort design) 2) TIEPOC-study (randomised controlled trial). Interventions: intervention-A (ad-hoc leaflet with instructions about correct IT according Spanish Respiratory Society), intervention B (intervention A+ individual training by instructors). Four visits were performed (baseline, 3, 6 and 12 months). Data on IT, sociodemographic and clinical characteristics, quality of life and respiratory drugs were recorded. Analysis under intention to treat principle. Multivariate analysis was conducted to measure the potential modifying factors of improvement in the IT along follow-up. Results: 660 patients (90.9%) did not perform a correct IT at baseline 89.75% with Handihaler, 86.95% with Turbuhaler, 84.75% with Accuhaler and 87.35% with pMDI. At 12 months, 221 patients 29.9% performed correctly the IT; a decrease in the slope of the curve (correct IT) was detected at 3 months follow-up. Intervention B was the most effective in both trials compared to control group or intervention A, regardless of preferences: 1) TECEPOC Study (preference trial): Intervention B versus control group, NNT = 3.22 (IC95%, 2.27–5.52); and versus Intervention A, NNT = 3.57 (CI95%, 2.41–6.8). Preferences improved 6.7% in the correct IT without statistical significance. 2) TIEPOC Study (randomized controlled trial): Intervention B versus control group, NNT = 1.74 (IC95%, 1.47–2.17), and versus intervention A, NNT = 3.33 (CI 95%, 2.43–5.55). No differences were measured between Intervention A and control group. Conclusion: Individual training significantly improves IT. Reminders every 3 months are recommended. Preferences do not influence the intervention effectiveness.